Serous Microcystic Adenoma of Pancreas - Smita S. Pudale; Gopal A. Pandit; Sunita S. Dantkale; Ravish G. Fangari (Journal of Krishna Institute of Medical Sciences University)
Serous Microcystic Adenoma of Pancreas (SMCA) is a rare tumour of exocrine pancreas. It has a striking predilection for elderly women and consists of small cysts surrounding central stellate scar. Histologically cysts are lined by glycogen rich cuboidal epithelium. In view of its benign nature and excellent prognosis this tumour needs to be accurately diagnosed. This report documents two cases of SMCA occurring in 45 and 36 years old females.